Development of Connected Wheel Motion Experiment System with Remote Laboratory Based IoT using the Web - Rahmat Dito Tri Wicaksono; - Asrizal; - Yohandri; - Hufri; Rio Anshari (PILLAR OF PHYSICS, 2023)
Remote measurement is a trend that is in great demand today. The development of connected wheel motion experiment system with a remote laboratory is aimed at effectiveness in experimental activities. This research is based on the weaknesses of previous research that there is no login system, queuing system, and time limit for using the experimental system. Based on these weaknesses, this study provides a solution to the experimental system with a login system, queuing system, and time limit for using the device. The Design and Development (D&D) method is the method chosen in this study. From the data analysis it can be stated in general that there are two results in this study. The first result is the performance specification of the related wheel drive experimental system where the function of each component of the experimental system has a performance according to the function of each component. The second result is the accuracy and precision of the associated wheel motion experimental system. Accuracy results for concentric wheels, obtained an average accuracy of 97.19% and 98.23%. Accuracy for connected wheels to ropes obtained an average result of 98.28% and 98.98%. The results of the angular velocity precision test on concentric wheels obtained an average of 99.43% and 99.09%. The precision of the angular velocity obtained on the wheels connected by a rope is 99.68% and 97.78%